INTERNALIZED STIGMA AND STIGMATIZING CULTURAL BELIEFS ON PARENTING WITH MENTAL ILLNESS AMONG FEMALE PATIENTS WITH SCHIZOPHRENIA: A COMPARISON OF FEMALE PARENT VERSUS NON PARENT - Shettima, Falmata; Rabbebe, Isa; Wakawa , Ibrahim; Wakil , Musa (Global Journal of Health Sciences, 2022)
Purpose: Differences in cultural values, norms and conceptualization of mental illness may influence mental illness stigma differently across the globe. Both public and self stigma have widely been researched globally however, little is known about the specific experiences of stigma that females, and in particular mothers, with schizophrenia encounter as parents in Nigeria. The study aims to explore and compare internalized stigma among female parents and female non-parents. The secondary aim is to explore if any association exist between cultural beliefs on parenting with mental illness and internalized stigma among female patients with schizophrenia. Methodology: 142 female patients with schizophrenia attending the GOPD clinic at FNPH Maiduguri recruited through convenience sampling completed the study. They completed a socio-demographic questionnaire and a modified version of the Internalized stigma of Mental Illness Scale (ISMI). Analysis was done using Statistical Package for Social Sciences (SPSS). Differences in self stigma were compared using chi-square for categorical variables and student t- test for continuous variables. P-value was set at 0.05. Findings: A total of 65 (75.6%) female parents and 32 (57.1%) of female non parents with schizophrenia had high self stigma. Female parents had a statically significant higher level of self stigma on the alienation subscale as well as the total score. Myths and misconceptions about parenting with mental illness were rampant. Conclusion: Self stigma is more prevalent among female parents with schizophrenia, with cultural beliefs and practices playing an important role in influencing stigma of mental illness. Further research of the impact of cultural factors on stigma of mental illness and culture specific interventions should be explored to reduce self stigma among parents with mental illness.